Oxford Research Encyclopedia of Climate Science 2016
DOI: 10.1093/acrefore/9780190228620.013.355
|View full text |Cite
|
Sign up to set email alerts
|

Economic, Technological, and Organizational Factors Influencing News Coverage of Climate Change

Abstract: Over the past two decades, the global news industry has embarked upon a major project of economic, organizational, and technological restructuring. In organizational terms, successive waves of mergers and buyouts have yielded a global news landscape where most of the larger firms are owned by shareholders and run by executives whose singular focus is on rationalizing news production and improving profitability. Although in some cases, these shareholders and executives have used their authority to influence cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…This is particularly true in the US, where studies have revealed a decline in science and environmental reporting due to the growing pressure on the traditional business models of legacy media. This has led to the restructuring and downsizing of newsrooms, fewer beats, fewer specialist journalists, generalist rather than specialist reporters covering science and the environment, outsourcing to freelancers, the migration of specialist reporters to general assignments or other desks, less time for investigative reporting, and a need to produce more output for a greater variety of platforms (Boykoff & Yulsman, 2013; Friedman, 2015; Gibson, 2017). Similar developments have been identified in Canada (Callison & Tindall, 2017), although their extent is less clear due to a smaller number of available studies.…”
Section: The Changing Organizational Make‐up Of Climate Journalismmentioning
confidence: 99%
See 3 more Smart Citations
“…This is particularly true in the US, where studies have revealed a decline in science and environmental reporting due to the growing pressure on the traditional business models of legacy media. This has led to the restructuring and downsizing of newsrooms, fewer beats, fewer specialist journalists, generalist rather than specialist reporters covering science and the environment, outsourcing to freelancers, the migration of specialist reporters to general assignments or other desks, less time for investigative reporting, and a need to produce more output for a greater variety of platforms (Boykoff & Yulsman, 2013; Friedman, 2015; Gibson, 2017). Similar developments have been identified in Canada (Callison & Tindall, 2017), although their extent is less clear due to a smaller number of available studies.…”
Section: The Changing Organizational Make‐up Of Climate Journalismmentioning
confidence: 99%
“…Some have argued that niche sites generally only reach small audiences who are already well‐informed about climate change, resulting in echo‐chambers of like‐minded publics (Gibson, 2017). However, a recent survey of 40 countries suggests that specialist outlets covering climate issues rank third for general audiences as a source of climate news after television and online sites of major news organizations (Newman, 2020).…”
Section: The Changing Organizational Make‐up Of Climate Journalismmentioning
confidence: 99%
See 2 more Smart Citations
“…Journalists are important in the process of climate change communication. Even though journalists themselves are embedded in, and influenced by, different normative, organizational, and social layers in their work (Shoemaker & Reese, 1995; see also Engesser (2017) and Gibson (2017), even though their position in public communication has changed from "gatekeeper" to "gatewatchers" (Bruns, 2008), and even though new journalistic role models have emerged (Allan, Fahy, & Nisbet, 2011), their impact on the selection of topics, stakeholders, and perspectives in media coverage is still considerable.…”
Section: Journalistic Framingmentioning
confidence: 99%